Kinematics and Workspace Analysis of an 8-DOF Space Manipulator - Kai Yang; Jinying Huang (Jixie chuandong)
An 8-DOF manipulator with prismatic pair is proposed for space environment， which can complete equipment maintenance and object grabbing in space environment. The pose transformation matrix and forward kinematics equation of 8-DOF manipulator are derived by standard D-H parameter method. The simulation model of the manipulator is established by Matlab robotics toolbox， and the simulation model is compared with the kinematics equation of the manipulator. Monte Carlo method is used to solve the workspace of the manipulator， and the point cloud of the workspace of the end effector of the manipulator is drawn. The trajectory planning of the manipulator is simulated by Matlab， and the displacement， velocity and acceleration curves of each joint in the motion process are drawn. The rationality of the structure design of the manipulator is verified， it provides a reference for the follow-up research work.